Information entropy in cosmological inference problems - Pinho, Ana Marta; Reischke, Robert; Teich, Marie; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2021)
ABSTRACT. The subject of this paper is a quantification of the information content of cosmological probes of the large-scale structures, specifically of tempera
Gesehen am 02.07.2021